Application of construal level and value-belief norm theories to undergraduate decision-making on a wildlife socio-scientific issue. Issue 9 (13th June 2018) - Sutter, A. McKinzie; Dauer, Jenny M.; Forbes, Cory T.
ABSTRACT: One aim of science education is to develop scientific literacy for decision-making in daily life. Socio-scientific issues (SSI) and structured decision-making frameworks can help students reach these objectives. This research uses value belief norm (VBN) theory and construal level theory (CLT) to explore students' use of personal values in their decision-making processes and the relationship between abstract and concrete problematization and their decision-making. Using mixed methods, we conclude that the level of abstraction with which students problematise a prairie dog agricultural production and ecosystem preservation issue has a significant relationship to the values students used in the decision-making process. However, neither abstraction of the problem statement nor students' surveyed value orientations were significantly related to students' final decisions. These results may help inform teachers' understanding of students and their use of a structured-decision making tool in a classroom, and aid researchers in understanding if these tools help students remain objective in their analyses of complex SSIs.